The Qur'anic miracle in theological thought Contemporary philosophical study - Dr. Nahreen Karim Kadham Al-Mayali (Zien Journals, 2021)
No one doubts that the Holy Qur’an is a book revealed to the chest of Muhammad (peace be upon him) and that it is the most incapable of eloquence in all ages until the present time. For all of this, what prompted me to search for the secret of this miraculousness in the Holy Book from the philosophical and verbal aspect, so I explained the types of miraculousness that are recognized in researchers’ books and articles, and then I referred to the conditions of the miraculous so that the researcher or reader would be aware of the concept of the miraculous. That is why the revelation of the Qur’an astonished every intelligent person at the time of the revelation and completion of the Glorious Qur’an. Indeed, through research, it was shown that it is a glorious book that falsehood does not come to it from before it, because it is a revelation from the Almighty, the All-Powerful. The Holy Book carried faith, philosophical, and deep verbal terms that astonished all Arabs when they heard and read it, as it put forward philosophical concepts through the noble verses and they were truly honest premises that necessarily produced truthful results.
Keywords: Miracles; letters; inference; reason